2020
DOI: 10.3390/vaccines8030353
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Vaccination with UV-Inactivated Chlamydia suis in Pre-Exposed Outbred Pigs Decreases Pathogen Load and Induces CD4 T-Cell Maturation into IFN-γ+ Effector Memory Cells

Abstract: Chlamydia trachomatis (Ct) infections are the most frequent bacterial sexually transmitted disease, and they can lead to ectopic pregnancy and infertility. Despite these detrimental long-term sequelae, a vaccine is not available. Success in preclinical animal studies is essential for vaccines to move to human clinical trials. Pigs are the natural host to Chlamydia suis (Cs)—a chlamydia species closely related to Ct, and are susceptible to Ct, making them a valuable animal model for Ct vaccine developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…This strain was isolated in the late 1960s from the faeces of an asymptomatic Austrian pig [ 40 ] and is considered the type strain [ 1 ]. C. suis S45 was successfully used in several experimental studies in pigs before [ 10 , 41 , 42 ], but never in ocular infection trials.…”
Section: Methodsmentioning
confidence: 99%
“…This strain was isolated in the late 1960s from the faeces of an asymptomatic Austrian pig [ 40 ] and is considered the type strain [ 1 ]. C. suis S45 was successfully used in several experimental studies in pigs before [ 10 , 41 , 42 ], but never in ocular infection trials.…”
Section: Methodsmentioning
confidence: 99%
“…The C. suis species-specific peptide antigens as well as the protocol of running peptide ELISA were used as previously validated and described [ 30 , 34 ]. C. suis peptide antigens were chemically synthesized with N-terminal biotin followed by a serine-glycine-serine-glycine spacer mixture Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Because quantifying IFN-γ production in T-cell phenotypes is less standardized than NA titer quantification, we will only compare IFN-γ production results from our lab in isolated peripheral blood mononuclear cells taking into account the different antigen restimulation. In a Chlamydia suis vaccination study, we observed vaccinated gilts with a significant response at approximately 0.5% of CD4 + T cells upon antigen restimulation [ 172 ]. In our two challenge studies in nursery pigs, we observed the strong CD4 + T-cell responders to be closer to 0.25% IFN-γ + upon antigen restimulation [ 67 , 129 ] with the exception of one group that responded close to 0.5% [ 129 ].…”
Section: Plotkin’s Principles Of Correlates Of Protection Applied To ...mentioning
confidence: 99%